Change-of-Direction Ability, Linear Sprint Speed, and Sprint Momentum in Elite Female Athletes: Differences Between Three Different Team Sports. Issue 1 (15th January 2022) - Freitas, Tomás T.; Pereira, Lucas A.; Alcaraz, Pedro E.; Comyns, Thomas M.; Azevedo, Paulo H.S.M.; Loturco, Irineu
Abstract: Freitas, TT, Pereira, LA, Alcaraz, PE, Comyns, TM, Azevedo, PHSM, and Loturco, I. Change-of-direction ability, linear sprint speed, and sprint momentum in elite female athletes: differences between three different team sports. J Strength Cond Res 36(1): 262–267, 2022—The aim of this study was to compare the performance of elite female players from 3 different sports in linear sprint and change-of-direction (COD) tests and examine their efficiency for changing direction through the calculation of the COD deficit (i.e., the difference in velocity between a linear sprint and a COD task of equal distance). One hundred fifty-four elite players (rugby, n = 40, national team members; soccer, n = 57 and handball n = 57, first division players from the respective Brazilian National Championships) were assessed in the 20-m linear sprint and Zigzag COD tests. A one-way analysis of variance with a Tukey post hoc was used to detect between-sport differences. Female rugby sevens players achieved faster sprint velocities than handball (20‐m: 6.21 ± 0.24 m·s −1 ; 6.07 ± 0.27 m·s −1, respectively; p < 0.05) and soccer players (5‐m: 4.71 ± 0.26 m·s −1 vs. 4.51 ± 0.20 m·s −1 ; and 20‐m: 6.08 ± 0.19 m·s −1 ; p < 0.05) and exhibited the greatest COD deficits (2.95 ± 0.25 m·s −1 ; 2.69 ± 0.19 m·s −1 ; 2.82 ± 0.17 m·s −1, for rugby, handball, and soccer, respectively; p < 0.05). Handball players outperformed all other athletes in the Zigzag test (3.38 ± 0.15 m·s −1 ; 3.26 ± 0.10 m·s −1 ; 3.26 ± 0.10 m·s −1, for handball, rugby, and soccer, respectively; p < 0.05) but presented the lowest COD deficits ( p < 0.05). Furthermore, soccer players displayed inferior sprint momentum when compared with the other sports ( p < 0.05). Linear sprint and COD ability differ significantly among elite female athletes from different team sports, with handball players exhibiting a greater COD speed and efficiency to change direction, with respect to their maximum sprint velocity. The between-sport differences observed suggests that specific training and game demands may affect both sprint and COD performance.